2002
DOI: 10.2139/ssrn.313643
|View full text |Cite
|
Sign up to set email alerts
|

Rolling-Sample Volatility Estimators: Some New Theoretical, Simulation and Empirical Results

Abstract: CIRANOLe CIRANO est un organisme sans but lucratif constitué en vertu de la Loi des compagnies du Québec. Reproduction partielle permise avec citation du document source, incluant la notice ©. Short sections may be quoted without explicit permission, provided that full credit, including © notice, is given to the source. ISSN 1198-8177Ce document est publié dans l'intention de rendre accessibles les résultats préliminaires de la recherche effectuée au CIRANO, afin de susciter des échanges et des suggestions. R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
104
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(104 citation statements)
references
References 50 publications
(55 reference statements)
0
104
0
Order By: Relevance
“…proposed by Foster & Nelson (1996) and Andreou & Ghysels (2002) in the univariate case, and later extended to the multivariate case in Fleming, Kirby & Ostdiek (2001), to the present setting. Thus, let Σ t andΣ t be short-hand notation for the latent conditional quadratic covariation matrix and a generic estimator of this, respectively.…”
Section: Measuring Quadratic Covariationmentioning
confidence: 82%
“…proposed by Foster & Nelson (1996) and Andreou & Ghysels (2002) in the univariate case, and later extended to the multivariate case in Fleming, Kirby & Ostdiek (2001), to the present setting. Thus, let Σ t andΣ t be short-hand notation for the latent conditional quadratic covariation matrix and a generic estimator of this, respectively.…”
Section: Measuring Quadratic Covariationmentioning
confidence: 82%
“…Since an ARCH model implies an AR model for the squared residuals 2 t , [33] showed that a simple Lagrange multiplier (LM) test for ARCH effects can be constructed based on the auxiliary regression (5). Under the null hypothesis that there are no ARCH effects,…”
Section: Testing For Arch/garch Effectsmentioning
confidence: 99%
“…This technique is based on the work of Foster and Nelson (1996) and Andreou and Ghysels (2002). The daily conditional covariance matrix based on high-frequency data is:…”
Section: Models For Conditional Covariance Matricesmentioning
confidence: 99%